The Tradition of Cultivation Theory And The Spiral of Silence Media - I Made Suyasa; Putu Indah Dianti Putri; Putu Suparna (COMMUSTY Journal of Communication Studies and Society, 2022)
The importance of understanding cultivation theory, we can analyze how the mass media work in forming opinions and be able to turn those opinions into public opinion so that the mass media are able to create homogeneous thoughts on situations or world realities. The research method or data collection is based on book dissection and several previous studies. From the results of this study, it can be concluded that the mass media make a major contribution to the perspective of each individual who basically has different perceptions to become homogeneous or the same view is all the effects of the cultivation process. Factors that influence the expression of one's opinion: ages, gender, economy levels, and educational stage including spiral of silence. Another effect of the cultivation process is the phenomenon of choosing to be silent from some individuals who have different views from public opinion, in other words, this phenomenon is called the spiral of silence.